Controllable synthesis of superparamagnetic NiCo-graphene quantum dot-graphene composite with excellent dispersion for high performance magnetic field-controlled electrochemical flow hybrid supercapacitor. (1st September 2020) - Keyang, He; Ruiyi, Li; Zaijun, Li; Yongqiang, Yang
Abstract: The in-situ formation, fixation and structural control of metal nanoparticles on graphene sheets are crucial issue to fabricate metal-graphene composite with high electrochemical performance. The study reports the synthesis of superparamagnetic NiCo-graphene quantum dot-graphene composite (NiCo-GQD-G). Histidine-functionalized graphene quantum dots (GQDs) were immobilized on graphene sheets of graphite oxide (GO) to form GQD-GO hybrid via π-π stacking. The hybrid are combined with Ni 2+ and Co 2+ to produce NiCo-GQD-GO complex. Followed by thermal reduction and partial oxidation. The resulting NiCo-GQD-G has a well-defined three-dimensional structure, monodispersity and superparamagnetic. NiCo nanocrystals were covered by NiO and CoO to produce core-shell structure with average particle size of 7.2 nm. The nanostructure can be effectively adjusted by varying the mass ratios of GQD/GO and NiCo/GO. The unique architecture promotes enhanced electron/ion conductivity, catalytic activity and magnetofluid property. The NiCo-GQD-G was adsorbed on nickel foam by magnet to make an electrode without any binder and conductive agent. The electrode exhibits high capacity (1808 F g −1 at 1 A g −1 ), rate-capacity (1525 F g −1 at 10 A g −1 and 900 F g −1 at 200 A g −1 ) and cycling stability (99.2% of capacity retention after 5000 cycles at 10 A g −1 ) in 3.0 M KOH electrolyte. The flow hybrid supercapacitor provides energy density of 247.4 W h kg −1 at power density of 6596 W kg −1 and 111.2 W h kg −1 at power density of 160100 W kg −1 . The synthesis can be also used for construction of other metal-graphene composites with excellent dispersion and controllable nanostructure. Graphical abstract: Image 1 Highlights: We reported one concept for synthesis of NiCo-graphene quantum dot-graphene hybrid. The hybrid offers excellent 3D structure, monodispersity and superparamagnetic. The hybrid show high electron/ion conductivity, catalytic activity and magnetofluid. The hybrid exhibits high specific capacitance, rate-capacity and cycling stability. The flow supercapacitor based on hybrid gives high energy density and power density.